2001
DOI: 10.1002/ijc.1220
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by arsenic trioxide in leukemia U937 cells is dependent on activation of p38, inactivation of ERK and the Ca2+-dependent production of superoxide

Abstract: The mechanism of the induction of apoptosis by arsenic trioxide (As 2 O 3 ), which was demonstrated recently to be an effective inducer of apoptosis in patients with leukemia, was examined in detail in human leukemia U937 cells. Upon treatment of U937 cells with 50 M of As 2 O 3 , complete inactivation of the kinases ERK1 and ERK2 was detected within 30 min. p38 was activated within 3 hr, and the maximum activity was detected at 6 hr, when DNA fragmentation remained undetectable. Experiments with transfected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 43 publications
6
89
1
Order By: Relevance
“…It is believed that damage due to arsenic is closely associated with oxidative stress induced by arsenic. As reported in earlier studies, arsenic is known to cause generation of free radicals, like reactive oxygen species (ROS) and reactive nitrogen species (RNS), as well as metabolic intermediates like dimethyl arsenic (DMA) peroxy radical [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 85%
“…It is believed that damage due to arsenic is closely associated with oxidative stress induced by arsenic. As reported in earlier studies, arsenic is known to cause generation of free radicals, like reactive oxygen species (ROS) and reactive nitrogen species (RNS), as well as metabolic intermediates like dimethyl arsenic (DMA) peroxy radical [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 85%
“…Activation of p38 MAPK has been shown to associate with ATO-induced apoptosis of human leukemic cell lines, U937 and K562 cells (31,32,35). To determine whether or not p38 MAPK is required for ATO-induced apoptosis of NB4 cells, the cells were untreated or treated with ATO (10 M) in the absence (DMSO alone) or presence of the p38 MAPK inhibitor SB203580 (10 M), and 24 h after incubation, apoptotic cells were scored (see "Experimental Procedures").…”
Section: Activation Of Chk2 and P38 Mapk In An Aplmentioning
confidence: 99%
“…It has been shown that p38 MAPK stimulates p53 in response to various stress agents, including UV irradiation and anticancer drugs, and regulates both activation of p53-mediated transcription and p53-dependent apoptosis (29,30). ATO is known to activate p38 MAPK in various neoplastic cell lines, suggesting a role for this pathway in the regulation of ATO-induced responses in malignant cells (31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…We and others groups have previously demonstrated that generation of ROS is an important event that mediates ATO-induced apoptosis. 30,[47][48][49][50] It is known that increased ROS may lead to activation of the PI3K/Akt survival pathway, which likely reflects a cellular response to ROS stress in the attempt to survive the drug insult. Furthermore, a recent study suggests that the PI3K/Akt signaling pathway may contribute to resistance to ATO-induced apoptosis in human leukemia cell lines.…”
Section: -Aag and Drug Combination In Leukemiamentioning
confidence: 99%